Effects of liver cirrhosis and patient condition on clinical outcomes in intrahepatic cholangiocarcinoma: a retrospective analysis of 156 cases in a single center - Jesper, Daniel; Heyn, Sabrina; Schellhaas, Barbara; Pfeifer, Lukas; Görtz, Rüdiger; Zopf, Steffen; Neurath, Markus; Strobel, Deike (European Journal of Gastroenterology & Hepatology, 2018)
OBJECTIVE: The incidence of intrahepatic cholangiocarcinoma (iCCA) has been increasing over the past few decades. Liver cirrhosis is an independent risk factor for the development of iCCA. This study aimed to examine the prognostic impact of liver cirrhosis and patient condition on the treatment of iCCA. PATIENTS AND METHODS: We retrospectively analyzed the cases of 156 patients diagnosed with iCCA between 1990 and 2014 in our center. Patients were divided into subgroups depending on the presence and severity of liver cirrhosis and the type of treatment. Clinical data, patient characteristics, and overall survival were compared between these groups. RESULTS: Forty-seven (30%) of 156 patients had liver cirrhosis, predominantly with Child-Pugh scores A (n=27) and B (n=12). The median survival differed between patients receiving tumor resection (34 months), chemotherapy (10 months), and best supportive care (2 months). An Eastern Cooperative Oncology Group Performance Status score more than 1 was a predictor of poor survival in all patients (P<0.001), independent of the presence of cirrhosis. Resection could be performed less frequently in cirrhotic patients (6 vs. 31 patients; P=0.04). If resection was performed, the presence of cirrhosis A/B did not influence survival. Cirrhosis A/B did not influence the outcome in patients receiving chemotherapy either. In cirrhotic patients receiving chemotherapy, cancer antigen 19-9 levels above 129 U/ml were associated with a significantly shorter survival (22.5 vs. 3 months, P=0.0003). CONCLUSION: The presence of liver cirrhosis in iCCA has been underestimated. There was no difference in survival between noncirrhotic patients and patients with compensated cirrhosis. Patients' general condition seems to be of more prognostic value in the treatment of iCCA than the presence of cirrhosis. Therefore, the presence of cirrhosis A/B should not prevent patients with a good Eastern Cooperative Oncology Group Performance Status score from receiving tumor resection or chemotherapy.
EVALuna2:34071